Patterns of Political Communication Between Government Institutions and Effect to the Trust of the Acehnese People - Ali, Muhammad; Anismar, A; Rizwan, M.; Fajri, F; Mursalin, M (International Journal for Educational and Vocational Studies, 2022)
This study has described how the pattern of political communication between government institutions and its impact on public confidence in development in Aceh Province, Indonesia. This study focuses more on the analysis of communication patterns between the executive (ie: Governor of Aceh Province) and the legislative (DPR) in carrying out their respective duties and functions in the context of development in Aceh Province, Indonesia. This study uses a descriptive qualitative approach aimed at describing the pattern of political communication between government institutions and analyzing the level of trust of the Acehnese people. The benefit of this study is to provide a formula for good and effective political communication with elites at various levels of institutions from the executive to the legislature. Based on the results of the study, it can be concluded that the patterns of political communication between government institutions, namely the executive and legislative institutions, are personal communication patterns, informal communication patterns, family communication patterns, party or organizational communication patterns. All types of communication patterns are carried out between parties in carrying out interest lobbying and development policies in the Aceh Province, Indonesia. This type of communication pattern, based on the results of research, has been carried out by both parties in running government institutions in Aceh, namely the Aceh Government and the Aceh Legislature.